Agarose gel implant with good injection performance

By using BDDE in buffer solution for chemical cross-linking treatment of agarose hydrogel, the problem of large thrust drop during injection was solved, and better injection and durability were achieved, and its implantation agent in skin was expanded. application potential.

CN119455104APending Publication Date: 2025-02-18SUZHOU SUMEI MEDICAL TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311002876.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Due to its high gel strength and viscosity, agarose autogels lead to a large drop in the thrust during injection, which limits its application in skin implants.

Method used

By using 1,4-butanediol diglycidyl ether (BDDE) as the crosslinking agent, chemical crosslinking is performed in a buffer solution, temperature is controlled for reaction, forming a hydrogel with new characteristics, and homogenization is performed by dialysis. to improve its injection performance.

Benefits of technology

This method significantly reduces the mechanical strength and viscosity of the agarose hydrogel, enhances its injectability, makes the thrust force during injection more uniform, reduces the force required for injection, and improves the application prospects of implants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455104A_ABST
    Figure CN119455104A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and particularly relates to an agarose gel implant with good injection performance. The preparation method comprises the following steps: dissolving agarose in a buffer solution at 90-120 DEG C to obtain a clear and transparent solution, cooling to 40-55 DEG C, adding alkali and a chemical cross-linking agent, stirring to react for 2-5 minutes, standing to react for 4-24 hours at 5-35 DEG C, and dialyzing and homogenizing to obtain the chemical cross-linked agarose hydrogel implant. Compared with agarose hydrogel formed by self-aggregation physical action, the agarose gel implant has better injection performance, and the injection chirality of an injection person and the comfort of an injected person are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to an agarose gel implant with good injection performance. Background Art

[0002] Skin implants can fill depressions, smooth wrinkles, increase skin elasticity, and make the skin glow with youth and health. FDA-approved skin implants must be injected through a needle syringe. Good injectability is a key property of implants, and implants need to ensure accuracy and safety of injection. During the injection process of the implant, uniform squeezing force is an important property of its good injectability. By applying uniform squeezing force, it can be ensured that the implant is evenly distributed during the injection process, avoiding uneven deposition or aggregation, and enhancing the hand fit during injection. Therefore, uniform injectability is an important consideration when selecting and developing implants.

[0003] Agarose is a biocompatible polysaccharide extracted from marine red algae, with repeating units of β-D-galactose and 3,6-anhydro-α-L-galactose disaccharide. Agarose has controllable self-gelling properties, and can be prepared into a thermoreversible self-aggregating gel after being dissolved at high temperature and cooled to about 37°C. Agarose gel also has adjustable mechanical properties, biodegradability, and non-immunogenic properties, which make it widely used in biomedical applications. However, due to the high gel strength and viscosity of agarose self-gel, especially high-concentration hydrogels, the large difference in extrusion force during injection makes it difficult to be injected, limiting the application of agarose in skin implants. Therefore, it is of great significance to develop agarose hydrogels with excellent injection properties.

[0004] The inventor unexpectedly discovered an optimized agarose preparation method, using 1,4-butanediol diglycidyl ether (BDDE) as a cross-linking agent, and chemically cross-linking in a buffer solution by controlling the temperature. The agarose forms a hydrogel with new properties, which can be directly used for injection after dialysis homogenization. This preparation process is simple and efficient. The chemically cross-linked agarose hydrogel has better injectability, and the extrusion force is gentle and uniform. The injector can use a smaller extrusion force to inject the agarose hydrogel into the patient's skin through an injection needle. At the same time, the chemically cross-linked agarose hydrogel maintains a durability similar to that of the self-aggregated agarose hydrogel, and its enhanced injection performance gives it a better implant application prospect. Summary of the invention

[0005] In view of the above technical problems, the object of the present invention is to provide an agarose gel implant with good injection performance. Specifically, the present invention includes the following contents:

[0006] In a first aspect, the present invention provides an agarose gel implant with good injection performance, and the preparation method of the agarose gel implant comprises the following steps:

[0007] (1) Dissolve agarose in a buffer solution at 90-120°C to obtain a clear and transparent solution A;

[0008] (2) cooling the solution A in step (1) to 40-55° C. to obtain solution B;

[0009] (3) adding a base and a chemical crosslinking agent to the solution B in step (2), stirring and reacting for 2-5 minutes to obtain a uniform solution C;

[0010] (4) The solution C in step (3) is allowed to react at 5-35° C. for 4-24 hours, and then dialyzed and homogenized to obtain an agarose gel implant.

[0011] Preferably, the temperature in step (1) is 100-110°C.

[0012] Preferably, the temperature in step (2) is 43-50°C.

[0013] Preferably, the temperature in step (4) is 25°C.

[0014] Preferably, the stirring reaction time in step (3) is 3-5 min.

[0015] Preferably, the pH of the buffer solution in step (1) is 6.5 to 7.5.

[0016] Preferably, the pH of the buffer solution in step (1) is 7.0.

[0017] Preferably, the buffer solution is a phosphate buffer solution.

[0018] Preferably, the phosphate buffer solution is a sodium dihydrogen phosphate solution, a disodium hydrogen phosphate solution or a mixed solution of the two.

[0019] Preferably, the base is selected from any one of sodium carbonate, sodium bicarbonate and sodium hydroxide.

[0020] Preferably, the base is sodium hydroxide.

[0021] Preferably, the mass percentage concentration of the sodium hydroxide is 0.1%-1%.

[0022] Preferably, the mass percentage concentration of the sodium hydroxide is 0.5%.

[0023] Preferably, the cross-linking agent is an epoxide cross-linking agent.

[0024] Preferably, the cross-linking agent is 1,4-butanediol diglycidyl ether.

[0025] Preferably, the mass percentage concentration of the 1,4-butanediol diglycidyl ether is 0.5%-2.5%.

[0026] Preferably, the mass percentage concentration of the 1,4-butanediol diglycidyl ether is 1.5%-2.5%.

[0027] Preferably, the mass percentage concentration of the 1,4-butanediol diglycidyl ether is 1.5%.

[0028] Preferably, the content of agarose is 10-25 mg / mL.

[0029] The beneficial effects of the present invention are as follows: ① The agarose hydrogel implant LTA-BDDE of the present invention is prepared by cross-linking BDDE at a temperature lower than the gelation temperature of agarose (<37°C), thereby retaining the excellent properties of agarose hydrogel and having reduced mechanical strength and viscosity, thereby enhancing its injectability; ② LTA-BDDE realizes uniform injection of agarose implants, effectively solves the problem of uneven injection force of LTA, and the injection force required for LTA-BDDE hydrogel is reduced; ③ Compared with BDDE hydrogel prepared by chemical cross-linking at a temperature higher than the gelation temperature of agarose (>37°C), the LTA-BDDE prepared by the present invention has better durability; ④ LTA-BDDE hydrogel has good durability similar to that of LTA gel and significantly enhanced injection performance, and has broad application potential in injection and implantation into the skin. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Storage modulus and loss modulus of agarose hydrogels prepared with different BDDE dosages;

[0031] Figure 2 The extrusion force diagram of agarose hydrogel prepared with different BDDE dosages;

[0032] Figure 3 Fourier transform infrared spectroscopy of agarose hydrogel;

[0033] Figure 4 Injection force diagram of agarose hydrogel;

[0034] Figure 5 Storage modulus and loss modulus plots of agarose hydrogel;

[0035] Figure 6 Shear viscosity diagram of agarose hydrogel;

[0036] Figure 7 Acid degradation rate graph of agarose hydrogel;

[0037] Figure 8 SEM image of agarose hydrogel. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with embodiments and drawings, but the present invention is not limited by the following embodiments.

[0039] Example 1 Preparation of agarose hydrogel

[0040] 1. Preparation of LTA-BDDE Hydrogel

[0041] 0.1 g of agarose was dissolved in 10 mL of PBS buffer solution (pH 7.0) at 100°C, stirred and refluxed for 30 min, then cooled to 43°C, 0.5% NaOH and 1.5% BDDE were added, and stirred for 3 min. The above homogeneous solution was allowed to react at 25°C for 24 h, then dialyzed in PBS buffer solution (pH 7.0), and the obtained gel was homogenized to obtain LTA-BDDE hydrogel with an agarose content of 10 mg / mL (1%).

[0042] 2. Preparation of LTA-BDDE Hydrogel

[0043] 0.25 g of agarose was dissolved in 10 mL of PBS buffer solution (pH 7.0) at 110°C, stirred and refluxed for 35 min, then cooled to 50°C, 0.5% NaOH and 1.5% BDDE were added, and stirred for 5 min. The above homogeneous solution was allowed to react at 25°C for 24 h, then dialyzed in PBS buffer solution (pH 7.0), and the obtained gel was homogenized to obtain LTA-BDDE hydrogel with an agarose content of 25 mg / mL (2.5%).

[0044] 3. Preparation of LTA Hydrogel

[0045] 0.1 g of agarose was dissolved in 10 mL of PBS buffer solution (pH 7.0) at 100° C., stirred and refluxed for 30 min, and then the solution was allowed to react at 37° C. for 24 h. The resulting gel was homogenized to obtain an LTA hydrogel with an agarose content of 10 mg / mL (1%).

[0046] 0.25 g of agarose was dissolved in 10 mL of PBS buffer solution (pH 7.0) at 110° C., stirred and refluxed for 35 min, and then the solution was allowed to react at 37° C. for 24 h. The resulting gel was homogenized to obtain an LTA hydrogel with an agarose content of 25 mg / mL (2.5%).

[0047] 4. Preparation of BDDE Hydrogel

[0048] 0.1 g of agarose was dissolved in 10 mL of PBS buffer solution (pH 7.0) at 100°C, stirred and refluxed for 30 min, then cooled to 55°C, 0.25% NaOH and 1.5% BDDE were added, and stirred for 3 min. The above homogeneous solution was allowed to react at 55°C for 24 h, then placed in PBS buffer solution (pH 7.0) for washing, and the water was changed every 4-8 h for a total of 24 h. The obtained gel was homogenized to obtain a BDDE hydrogel with an agarose content of 10 mg / mL (1%).

[0049] 0.25 g agarose was dissolved in 10 mL PBS buffer solution (pH 7.0) at 110°C, stirred and refluxed for 35 min, then cooled to 50°C, 0.25% NaOH and 1.5% BDDE were added, and stirred for 5 min. The above homogeneous solution was allowed to react at 55°C for 24 h, then placed in PBS buffer solution (pH 7.0) for washing, and the water was changed every 4-8 h for a total of 24 h. The obtained gel was homogenized to obtain a BDDE hydrogel with an agarose content of 25 mg / mL (2.5%).

[0050] Example 2 Preparation of Agarose Hydrogel Freeze-Dried Sponge

[0051] The 1% LTA-BDDE, 2.5% LTA-BDDE, 1% LTA, 2.5% LTA, 1% BDDE, and 2.5% BDDE agarose hydrogels prepared in Example 1 were pre-frozen at low temperature for 14 hours, and vacuum freeze-dried for 24 hours to form freeze-dried agarose hydrogel sponges, respectively.

[0052] Example 3 Effect of reaction temperature on the preparation of agarose hydrogel

[0053] 0.1 g of agarose was dissolved in 10 mL of PBS buffer solution (pH 7.0) at 105°C, stirred and refluxed for 30 min, then cooled to 45°C, 0.5% NaOH and 1.5% BDDE were added, and stirred for 3 min. The above uniform solution was reacted at 5°C, 15°C, 25°C, 35°C, 45°C, 55°C, 65°C, 75°C, 85°C, 95°C and 105°C for 24 h to obtain a reaction product.

[0054] At 85℃, 95℃ and 105℃, the reaction product is still a transparent solution and cannot form a hydrogel. At 45℃, 55℃, 65℃ and 75℃, the reaction product forms a gel, indicating that agarose hydrogel can be formed by BDDE chemical crosslinking under the temperature condition of 45℃-75℃. At 5℃, 15℃, 25℃ and 35℃, the reaction product forms a gel, indicating that agarose hydrogel can be formed under the combined action of hydrogen bond physical action and BDDE chemical crosslinking.

[0055] Example 4 Effect of BDDE Dosage on Preparation of Agarose Hydrogel

[0056] 0.1 g agarose was dissolved in 10 mL PBS buffer solution (pH 7.0) at 105°C, stirred and refluxed for 30 min, then cooled to 45°C, 0.5% NaOH was added, and 0.5%, 1%, 1.5%, 2% and 2.5% BDDE were added respectively, and stirred for 3 min. The above uniform solution was reacted at 25°C for 24 h to obtain the reaction product. The rheological mechanics and injectability test results of the product are shown in Figure 1 and 2 shown.

[0057] In the reaction product at 25°C, 0.5%, 1%, 1.5%, 2% and 2.5% BDDE can form gels, indicating that agarose hydrogels can be formed under the combined action of hydrogen bond physical action and 0.5%-2.5% BDDE chemical cross-linking. As the amount of BDDE increases, the mechanical strength of the gel decreases and the injectability increases. When the BDDE amount reaches 1.5%, the mechanical strength of the gel no longer changes and the injectability reaches the optimal level.

[0058] Example 5 Infrared Characterization of Agarose Hydrogel

[0059] The Fourier transform infrared spectrum of the freeze-dried sample of LTA-BDDE hydrogel prepared in Example 1 is as follows: Figure 3 As shown. 1000-1200cm -1 It is the CO stretching vibration peak, 1161cm after BDDE cross-linking -1 The peak at 2700-3000cm disappeared, indicating that the epoxy bond of BDDE reacted with the primary hydroxyl group of agarose to form ether, and the CO stretching vibration peak of the primary hydroxyl group (-CH2OH) turned into the CO stretching vibration peak of the ether bond (COC). -1 It is the CH stretching vibration peak, which is at 2900cm after BDDE cross-linking. -1 There is a split peak near the BDDE cross-linking, indicating that new CH bonds were introduced after BDDE cross-linking. These results show that BDDE successfully cross-linked agarose.

[0060] Example 6 Injectability test of agarose hydrogel

[0061] Test samples: 1% LTA-BDDE, 2.5% LTA-BDDE, 1% LTA, 2.5% LTA, 1% BDDE and 2.5% BDDE prepared in Example 1.

[0062] This test uses a needle-passing instrument to test the needle-passing property of the sample. During the test, the injection needle is installed and the core rod is pushed at a constant speed. The sample in the syringe is pushed out through the needle to obtain the pushing force curve. The pushing force curve shows the change of the pushing force during the sample extrusion process. The smaller the pushing force, the easier the sample is to be squeezed out and the better the injectability. The injectability test results are as follows: Figure 4 shown.

[0063] The results show that the push force curve of LTA gel has a certain drop, especially the high concentration of 2.5% LTA, indicating that the sample is unevenly dispersed, affecting the handiness during injection. This result was changed by chemical cross-linking of BDDE, and the push force of BDDE and LTA-BDDE gel during injection was more uniform and gentle, indicating that the sample was evenly dispersed. However, the push force of LTA-BDDE gel prepared by the present invention is the smallest, especially at high concentrations, which makes the injection of agarose implants easier and significantly improves the injectability of the implants.

[0064] Example 7 Rheological properties test of agarose hydrogel

[0065] The LTA-BDDE, LTA and BDDE gels of uniform thickness of 1 cm×1 cm×2 mm prepared in the examples were placed on the sample stage of the rheometer, the shear strain of the rheometer was fixed, and the storage modulus G' (Pa) and loss modulus G" (Pa) of the gels varying with angular frequency were tested.

[0066] The rheological mechanical properties test results of LTA-BDDE, LTA and BDDE gels are shown in Figure 5 As shown. When the angular frequency is 1.7rad / s, the storage modulus of 1% LTA is 18171Pa; the storage modulus of 1% LTA-BDDE is 2584Pa; the storage modulus of 1% BDDE is 591Pa; the storage modulus of 2.5% LTA is 90037Pa; the storage modulus of 2.5% LTA-BDDE is 15842Pa; and the storage modulus of 2.5% BDDE is 4926.8Pa. Compared with LTA, the storage modulus and loss modulus of LTA-BDDE are significantly lower, making it easier to inject.

[0067] Example 8 Shear viscosity test of agarose hydrogel

[0068] The LTA-BDDE, LTA and BDDE gels of uniform thickness of 1 cm×1 cm×2 mm prepared according to Example 1 were then placed on the sample stage of a rheometer and the rheometer was used to perform a shearing process at a shear rate of 0.01 s -1 ~1 000s -1 The peristaltic scanning was performed under the condition of , and the shear viscosity of different gels was obtained. The test results are shown in Figure 6 shown.

[0069] The results showed that the viscosity of LTA-BDDE, LTA and BDDE gels decreased with increasing shear rate, indicating that agarose gel has a shear thinning effect. Compared with LTA, the shear viscosity of BDDE did not decrease significantly, while the shear viscosity of LTA-BDDE decreased significantly. LTA-BDDE showed the most significant shear thinning effect, with the lowest viscosity and the least force required for injection.

[0070] Example 9 In vitro degradation test of agarose hydrogel

[0071] Test sample: freeze-dried sponge of Example 2

[0072] Weigh appropriate amounts (W0) of six freeze-dried sponges (1% BDDE, 1% LTA-BDDE, 1% LTA, 2.5% BDDE, 2.5% LTA-BDDE and 2.5% LTA) in centrifuge tubes, and allow them to reach swelling equilibrium in PBS buffer (pH 7.0). Then, soak them in PBS buffer containing 1.5 M hydrochloric acid at 37°C to characterize the degradation behavior of the hydrogels. Samples were taken at regular intervals, the supernatant was removed after centrifugation, and the precipitate was freeze-dried and weighed (W0). t The acid degradation rate was calculated according to the following formula: Weight loss (%) = (W0-W t ) / W0×100%, the result is as follows Figure 7 .

[0073] Compared with LTA gel, the degradation rate of BDDE gel is significantly accelerated and the durability is significantly reduced. The LTA-BDDE gel prepared by the present invention maintains good durability similar to that of LTA gel and can function for a longer period of time after implantation, similar to LTA gel.

[0074] Example 10 Scanning electron microscopy (SEM) characterization of agarose hydrogel

[0075] The LTA-BDDE, LTA and BDDE sponge samples prepared in Example 2 were fixed on the sample stage of a scanning electron microscope, sprayed with gold for 25 seconds, and then the sample morphology was detected using a scanning electron microscope at an operating voltage of 5.0 kV.

[0076] Scanning electron microscopy (SEM) results show Figure 8 As shown, compared with the significantly larger mesh structure of BDDE sponge, the mesh of LTA and LTA-BDDE sponges is denser, and their microscopic morphology is quite different from that of BDDE sponge.

[0077] In summary, the present invention uses 1,4-butanediol diglycidyl ether (BDDE) as a cross-linking agent to chemically cross-link agarose to obtain LTA-BDDE hydrogel regulated by self-aggregation physical effect and chemical cross-linking. Compared with the LTA hydrogel with self-aggregation physical effect, the agarose hydrogel prepared by the present invention has better injectability and more uniform injection force; the extrusion force required for injection of 2.5% LTA-BDDE hydrogel is significantly reduced, so that it can be better injected into the skin as an implant. At the same time, LTA-BDDE hydrogel has good durability similar to LTA gel, and can play a role for a longer period of time after implantation.

[0078] The above description is only the details of individual exemplary implementation cases of the present invention. For those skilled in the art, the present invention may have various modifications and changes according to specific preparation conditions during actual application, and is not intended to limit the present invention. Anything within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An agarose gel implant with good injection performance, characterized in that: The preparation method of the agarose gel implant comprises the following steps: (1) Dissolve agarose in a buffer solution at 90-120°C to obtain a clear and transparent solution A; (2) cooling the solution A in step (1) to 40-55° C. to obtain solution B; (3) adding a base and a chemical crosslinking agent to the solution B in step (2), stirring and reacting for 2-5 minutes to obtain a uniform solution C; (4) The solution C in step (3) is allowed to react at 5-35° C. for 4-24 hours, and then dialyzed and homogenized to obtain an agarose gel implant.

2. The agarose gel implant according to claim 1, characterized in that The pH of the buffer solution in step (1) is 6.5 to 7.

5.

3. The agarose gel implant according to claim 2, characterized in that: The pH of the buffer solution in step (1) is 7.

0.

4. The agarose gel implant according to claim 1, characterized in that: The buffer solution is a phosphate buffer solution.

5. The agarose gel implant according to claim 1, characterized in that: The alkali is selected from any one of sodium carbonate, sodium bicarbonate and sodium hydroxide.

6. The agarose gel implant according to claim 5, characterized in that: The base is sodium hydroxide.

7. The agarose gel implant according to claim 6, characterized in that: The mass percentage concentration of the sodium hydroxide is 0.1%-1%.

8. The agarose gel implant according to claim 1, characterized in that: The cross-linking agent is 1,4-butanediol diglycidyl ether.

9. The agarose gel implant according to claim 8, characterized in that: The mass percentage concentration of the 1,4-butanediol diglycidyl ether is 0.5%-2.5%.

10. The agarose gel implant according to claim 1, characterized in that: The content of the agarose is 10-25 mg / mL.

Citation Information

Cited By

  • Tissue-mimicking hydrogel material

    US12728184B2